Fibra Revirada en Cupresus Lusitánica - Vásquez, Flaminio; Diaz-Vaz, Juan E. (Bosque (Valdivia), 1985)
Spiral grain was found in two Cupressus lusitanica stands, 26 and 28 years old, growing in Valdivia, Chile. All of the studied trees showed spiral grain. The average twist was 4.6 degrees and 86.8% of the trees had a dextrorse spiral grain. Significative differences were found among trees. Stand differences appeared significative only on the north-south measurements of each tree within a stand. On the 58.2% on the trees, twist rate showed a decreasing trend with increasing age. It is concluded that it is not possible to associate external characteristics to degree and type of twist or spiral grain. It was regardless of the absence or presence of twist in the bark, wood can present varions degrees and types of spiral grain. In some stands and cardinal orientation, significative associations were found, between crown form and branch diameter with regard to spiral grain in the stem. Twist was bigger in trees with in irregular crown. Trees with in irregular crown. Trees with thin branches, had bigger twists than those with thich branches.